2016
DOI: 10.1080/10942912.2015.1086786
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic of Color Changes in Almond (Akbadem Variety) During Roasting and Storage

Abstract: In this research, the color change kinetics of Akbadem variety during roasting and storage processes was investigated. The roasting process was carried out at three different temperatures (150, 160 and 170 °C) and four different times as 10, 20, 30 and 40 minutes and then roasted samples were separated in two groups and stored six months in 4 °C and 22 °C. The color parameters for the color change of the materials were quantified by the Hunter L, a and b system. The all color parameters reactions during roaste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…However, the increase in b* value 30 min at 190°C was observed after which it was decreased due to the charring of the kernels. Similar findings were reported byBerk et al (2019) for sesame seed, wherein the loss of yellowness at the temperature higher than 180°C was recorded Nizamlioglu and Nas (2016). reported that the roasting of almond at temperatures 150, 160, 170°C for 40 min significantly increased the b* value.Özdemir and Devres (2000) did not find any trend for b* value in hazelnut roasting at 100-160°C.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…However, the increase in b* value 30 min at 190°C was observed after which it was decreased due to the charring of the kernels. Similar findings were reported byBerk et al (2019) for sesame seed, wherein the loss of yellowness at the temperature higher than 180°C was recorded Nizamlioglu and Nas (2016). reported that the roasting of almond at temperatures 150, 160, 170°C for 40 min significantly increased the b* value.Özdemir and Devres (2000) did not find any trend for b* value in hazelnut roasting at 100-160°C.…”
supporting
confidence: 87%
“…Lower E a values can be accredited to enhanced reaction rate and water mobility at higher roasting temperature. The lower activation energies previously reported by Chung et al (2014) for corn (34.04-79.16 kJ/mol) comparatively at higher temperature (160-180°C) and Nizamlioglu and Nas (2016)…”
Section: Activation Energymentioning
confidence: 60%
See 1 more Smart Citation
“…A number of studies on the kinetics of color change during roasting have been reported in peanuts (Moss & Otten, ; Shi, Sandeep, Davis, Sanders, & Dean, ), hazelnuts (Ozdemir & Devres, ), sesame seeds (Kahyaoglu & Kaya, ), cocoa beans (Krysiak, ), corn kernels (Chung, Kim, Moon, & Youn, ), coffee beans (Wang & Lim, ), almonds (Nizamlioglu & Nas, ) and many others. However, no published data is available correlating between salt‐coated paddy and the color of the popped rice from it.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies are being conducted currently on the possibility of using image analysis techniques for maturity and quality estimation of fruits, vegetables, as well as seeds. [32][33][34][35][36][37] In the present study, digital image analysis (DIA) was applied to evaluate the rapeseed maturity degree. Using this technique, the colour of seed surfaces and cross-sections and morphological size were determined for rapeseed samples harvested at different maturity stages.…”
Section: Introductionmentioning
confidence: 99%